2022
DOI: 10.3389/fphar.2022.1012294
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics and safety of the two oral cefaclor formulations in healthy chinese subjects in the fasting and postprandial states

Abstract: We conducted a phase I bioequivalence trial in healthy Chinese subjects in the fasting and postprandial states. The goal of this trial was to compare the pharmacokinetics and safety of the test preparation Cefaclor granule (Disha Pharmaceutical Group Co., Ltd.) and the reference preparation Cefaclor suspension (Ceclor®, Eli Lilly and Company). In this trial, 24 subjects were selected in the fasting and postprandial states, respectively. Enrolled subjects randomly accepted a single dose of 0.125 g Cefaclor gran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
1
1
0
Order By: Relevance
“…This study demonstrated a sensitive, rapid, and stable detection method with low plasma consumption. The pharmacokinetics study of healthy Chinese volunteers was carried out successfully using this method, and the pharmacokinetic parameters of cefaclor dry suspension were consistent with a previous report (Qu et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…This study demonstrated a sensitive, rapid, and stable detection method with low plasma consumption. The pharmacokinetics study of healthy Chinese volunteers was carried out successfully using this method, and the pharmacokinetic parameters of cefaclor dry suspension were consistent with a previous report (Qu et al, 2022).…”
Section: Discussionsupporting
confidence: 86%
“…SIL-IS was seldom used in previous assays of cefaclor quantification in human plasma (Chen et al, 2003(Chen et al, , 2012Huang, Cadwallader, & Heltsley, 2014;Jiang et al, 2009;Kai et al, 2003;Koytchev et al, 2004;Li et al, 2010;Lindgren, 1987;Naz et al, 2017;Qu et al, 2022;Tutunji et al, 2001). As an ideal method for precise quantification using LC-ESI-MS/MS (Huang, Cadwallader, & Heltsley, 2014), SIL-IS has almost similar physical and chemical properties, retention times, and ionization to the analyte (Liu et al, 2019;Loos et al, 2016).…”
Section: Pharmacokinetics Studymentioning
confidence: 99%
“…Should not be taken with food to allow optimal absorption [110] Amoxicillin Cmax decreased, Tmax prolonged under fed condition, but with no change of the AUC, thus use both under fasted and fed state is effective, since it is time-dependent AB [111] Amoxicillin-clavulanate Decreased bioavailability of clavulanic acid after meal (extended-release tablets), so administration before meal is preferrable [112] Flucloxacillin Reduced AUC, Cmax, and prolonged Tmax of both free and total concentrations compared with the fasting state. Achievement of free concentration targets associated with efficacy was in most circumstances equivalent, suggesting no negative association with the fed state [113] Cefaclor Cmax decreased, Tmax delayed, but no AUC changes were reported for cefaclor granule and cefaclor suspension under fed state supposing effective use regardless of meal [114] Cefuroxime axetil Positive food effect on absorption with AUC in fed state greater than in the fasted state, suggesting postprandial administration be more effective [109] Cefpodoxime proxetil Achievement of proper Cmax and MIC values was reported in non-fasting patients. In the elderly patients, the absorption is approximately 30% lower compared to younger patients [115][116][117] Azithromycin Capsules have delayed disintegration under fed state, resulting in the extended gastric residence and gastric degradation of azithromycin, thus capsules should be taken only in the fasted state.…”
Section: Drug (Oral Administration)mentioning
confidence: 94%